2009
DOI: 10.1073/pnas.0807854106
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Ebola VP35 interferon inhibitory domain

Abstract: Ebola viruses (EBOVs) cause rare but highly fatal outbreaks of viral hemorrhagic fever in humans, and approved treatments for these infections are currently lacking. The Ebola VP35 protein is multifunctional, acting as a component of the viral RNA polymerase complex, a viral assembly factor, and an inhibitor of host interferon (IFN) production. Mutation of select basic residues within the C-terminal half of VP35 abrogates its dsRNA-binding activity, impairs VP35-mediated IFN antagonism, and attenuates EBOV gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
195
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 145 publications
(203 citation statements)
references
References 38 publications
7
195
0
Order By: Relevance
“…Ebolavirus proteins contain a significant fraction (20%) of structurally disordered regions, and the fraction of variable positions in these regions is significantly higher (p < 0.01) than in the structurally ordered regions. The 3D structures of globular regions are mostly known (Table S2) [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] except for the N-terminal zinc-finger domain of VP30, the coiled-coil domain of VP35, and protein L. Identification and analysis of structurally characterized homologs allowed us to predict the structure of the zinc-finger domain in VP30, the overall topology of NP, and the structure and catalytic sites for the catalytic domains of protein L.…”
Section: Resultsmentioning
confidence: 99%
“…Ebolavirus proteins contain a significant fraction (20%) of structurally disordered regions, and the fraction of variable positions in these regions is significantly higher (p < 0.01) than in the structurally ordered regions. The 3D structures of globular regions are mostly known (Table S2) [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] except for the N-terminal zinc-finger domain of VP30, the coiled-coil domain of VP35, and protein L. Identification and analysis of structurally characterized homologs allowed us to predict the structure of the zinc-finger domain in VP30, the overall topology of NP, and the structure and catalytic sites for the catalytic domains of protein L.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structures of WT VP35 (PDB ID: 3FKE), which is a dipolymer that just contains the C-terminal domain of VP35, were obtained from the Protein Data Bank [15]. All of the crystal water molecules were deleted from the PDB file.…”
Section: Preparation Of Vp35-swcnt Complexesmentioning
confidence: 99%
“…VP35 consists in an N-terminal coiled-coil domain and a Cterminal domain termed the IFN inhibitory domain (IID) [12][13][14]. The C-terminal domain of VP35 includes two basic patches: the first basic patch (FBP) is important for interactions with EBOV nucleoprotein (NP) and VP35 polymerase cofactor function; the central basic patch (CBP) is important for VP35-dsRNA binding and IFN inhibition [14,15]. In the absence of VP35, no reported gene expression has been detected, while in the presence of optimal concentration of VP35, maximal reported gene activation has been detected [16,17].…”
mentioning
confidence: 99%
“…These include inhibition of IFN production through double-stranded (ds)RNA sequestration and inhibition of IFN regulatory factor (IRF) 3/IRF7 phosphorylation by direct association with kinases that activate IRF3/IRF7, IKKe/TBK-1 (13,15,21,25). Structural and biochemical studies on Zaire EBOV (ZEBOV) and Reston EBOV (REBOV) VP35 IFN inhibitory domains (IID) (termed zVP35 and zIID or rVP35 and rIID, for VP35 protein and IID, respectively) in free and dsRNA-bound forms identified a number of functionally critical basic residues (21,(26)(27)(28). These are located in the central basic patch (CBP) in the β-sheet subdomain and the first basic patch (FBP) in the α-helical subdomain (21,(26)(27)(28).…”
mentioning
confidence: 99%
“…Structural and biochemical studies on Zaire EBOV (ZEBOV) and Reston EBOV (REBOV) VP35 IFN inhibitory domains (IID) (termed zVP35 and zIID or rVP35 and rIID, for VP35 protein and IID, respectively) in free and dsRNA-bound forms identified a number of functionally critical basic residues (21,(26)(27)(28). These are located in the central basic patch (CBP) in the β-sheet subdomain and the first basic patch (FBP) in the α-helical subdomain (21,(26)(27)(28). Based on the dsRNA-bound structures of VP35 IIDs, it was suggested that these basic patches are important for protein-protein and protein-RNA interactions (21,27,28).…”
mentioning
confidence: 99%